HUBUNGAN ANTARA PENYAPIHAN DENGAN BERAT BADAN DI WILAYAH RW 03 KEDURUS KECAMATAN KARANGPILANG SURABAYA - Farida Umamah; Ayu Istikhomah (Universitas Nahdlatul Ulama Surabaya, 2015)
The relationship with weaning weight in the region of Kedurus RW 03 sub-district of Karangpilang Surabaya. ASI (mother’s milk) given mandatory in infants from birth, and when a baby enters the age to 6 months, baby food introduced on new companion. ASI (mother’s milk) could still be forwarded until the child is two years old. However, the phenomenon that there are many mothers who do the weaning age of 2 years. This research aims to analyze the relationship with weaning weight in the region of Kedurus RW 03 sub-district of Karangpilang Surabaya.The design used in this study was observational, analytic. The approach used in this study is a “Cross Sectional”. the entire research population mother who does weaning for 1 month in the region of 15 people with Simple Random Sampling techniques. The independent variable is the dependent variable and weaning weight. Instruments questionnaire and KMS, analyzed using test Chi – Square with significant levels of α = 0,05 .Result of research the majority of age of weaning <2 years and almost half of (66,6%) it down (46,6%). Chi - Square test analysis results showed, ρ = 0.042 >< α = 0.05 or ρ<α then, it can be concluded that H0 is denied, which means there is a relationship between weaning weight. This research, it could be concluded that there is a relationship between weaning weight. Mothers are expected to not only provide exclusive breastfeeding for 6 months, however, still have to be given for 2 years.> <α then, it can be concluded that H0 is denied, which means there is a relationship between weaning weight. This research, it could be concluded that there is a relationship between weaning weight. Mothers are expected to not only provide exclusive breastfeeding for 6 months, however, still have to be given for 2 years.